MODEL PENENTUAN KOMPETENSI INTI INDUSTRI DAERAH Studi Kasus Kabupaten Bangkalan - Indahsari, Kurniyati (IQTISHODUNA, 2010)
Presidential Decree No. 28/2008 on National Industrial Policy entrust each province/district developing their regional industrial core competency. However, there‘s no a standard guidelines on how to determine it except the characteristics of the regional core competency. This article tries to explain a model of determining regional industrial core competency using quantitative as well as qualitative approach. Stakeholders met in focus group discussions (qualitative approach) and gave their valuation on grade of competency of some regional industrial products using scoring method (quantitative approach). The result are (1) regional industrial core competence of Bangkalan district are Terung chips, Agel cord, traditional whip, batik, plait a mat and bird cage; and (2) Bangkalan industrial core competence is more characterized by resource based industries than market based industries